Pengaruh Struktur Modal Terhadap Kinerja Keuangan Pada PT. Astra Agro Lestari Tbk - Nindyawati (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2020)
This study aims to examine and analyze the structure consisting of capital, debt and investment on financial performance at PT. Astra agro lestari tbk. Data collection is carried out through financial reports that are available on the Indonesian stock exchange (BEI) for 5 years. Analysis of calculations in research using the help of SPSS 23 program. The sampling technique used is the population method and sampling. The data testing technique uses multiple linear regression, t test or partial, F test or simultaneous. The results of the analysis show that capital has a significant effect on financial performance, debt has a significant effect on financial performance, while investment has no significant effect on financial performance.